Echocardiographic Changes in Patients Implanted With a Fully Magnetically Levitated Left Ventricular Assist Device (Heartmate 3) - Uriel, Nir; Medvedofsky, Diego; Imamura, Teruhiko; Maly, Jiri; Kruse, Eric; Ivák, Peter; Sood, Poornima; Lang, Roberto M; Maffessanti, Francesco; Berliner, Dominik; Bauersachs, Johann; Haverich, Axel; et al. (Journal of cardiac failure, 2019)
BACKGROUND: The Heartmate 3 (HM3) is a Conformiteé Européenne mark-approved left ventricular (LV) assist device (LVAD) with fully magnetically levitated rotor and features consisting of a wide range operational speeds, wide flow paths, and artificial pulse. We performed a hemodynamic-echocardiographic speed optimization evaluation in HM3-implanted patients to achieve optimal LV- and right ventricular (RV) shape. METHODS AND RESULTS: Sixteen HM3 patients underwent pump speed ramp tests with right heart catheterization. Three-dimensional echocardiographic (3DE) LV and RV datasets (Philips) were acquired, and volumetric (Tomtec) and shape (custom software) analyses were performed (LV: sphericity, conicity; RV: septal and free-wall curvatures). Data were recorded at up to 13 speed settings. Speed changes were in 100-rpm steps, starting at 4600 rpm and ramping up to 6200 rpm. 3DE was feasible in 50% of the patients. Mean original speed was 5306 ± 148 rpm. LV end-diastolic (ED) diameter (-0.15 ± 0.09 cm/100 rpm) and volumes (ED: 269 ± 109 mL to 175 ± 90 mL; end-systolic [ES]: 234 ± 111 mL to 146 ± 81 mL) progressively decreased as the shape became less spherical and more conical; RV volumes initially remained stable, but at higher speeds increased (ED: from 148 ± 64 mL to 181 ± 92 mL; ES: 113 ± 63 mL to 130 ± 69 mL). On average, the RV septum became less convex (bulging toward the LV) at the highest speeds. CONCLUSIONS: LV and RV shape changes were noted in HM3-supported patients. Although a LV volumetric decrease and shape improvement was consistently noted, RV volumes grew in response to increase in speed above a certain point. A next concern would be whether understanding of morphologic and function changes in LV and RV during LVAD speed change assessed with the use of 3DE helps to optimize LVAD speed settings and improve clinical outcomes.
Keywords: Female; Heart Ventricles; ženské pohlaví; srdeční komory; Cardiac Catheterization; Heart Failure; Heart-Assist Devices; echokardiografie trojrozměrná; Magnetic Field Therapy; lidé; srdeční selhání; Echocardiography, Three-Dimensional; prospektivní studie; Male; podpůrné srdeční systémy; Aged; Prospective Studies; magnetoterapie; srdeční katetrizace; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans